Acoustoelastic guided wave propagation in axial stressed arbitrary cross-section. (14th March 2019) - Yang, Zhengyan; Wu, Zhanjun; Zhang, Jiaqi; Liu, Kehai; Jiang, Youqiang; Zhou, Kai
Abstract: This paper investigates the effect of axial stress on acoustoelastic guided wave propagation in arbitrary cross-section. Many researchers have investigated the effect of stress on guided wave propagation in arbitrary cross-section. However, the effect of high-order elastic constants in guided waves propagation of such structures is not as well understood. This paper deals with an acoustoelastic theory combined with semi-analytical finite element (AE-SAFE) method for modeling stressed wave propagation. The dispersive solutions are obtained in terms of phase velocities, group velocities and velocity sensitivities to stress variations in complex arbitrary cross-section. These results can be utilized to select the appropriate points and are significant for stress measure in arbitrary cross-section at high frequency region. The AE-SAFE method is applied to three examples, including plates, load bearing stringer and rail track.